Management Capacity In Peru: Obstacles, Requirements And Profiles - Michelsen, Carlos J. (Universidad del Pacífico, 1979)
The specific roles of the administrator would, for some, an important variation between countries due to their own situations of economic, social and cultural, that would be the main obstacle to the practice and teaching of administration in developing countries. This position has been called "administrative relativism" and it is necessary toanalyze the beginning of this exhibition.